PENGARUH MANAJEMEN SUMBER DAYA MANUSIA DALAM PENGELOLAAN LIMBAH TERHADAP KESEHATAN DAN KESELAMATAN KERJA KARYAWAN DI PT TIRTA ANUGRAH TIBAWA KABUPATEN GORONTALO - Rivaldo Kanter; Basmi Said; Wanny Tumewu (LPPM Sekolah Tinggi Ilmu Ekonomi Petra Bitung, 2026)
This study aims to analyze the influence of human resource management in waste management on occupational health and safety (K3) of employees at PT Tirta Anugrah Tibawa, Gorontalo Regency. Studies specifically integrating the role of HRM as a linking variable between waste management and occupational health and safety remain limited, indicating a research gap that needs further investigation. This study used a quantitative method with a survey approach. The sample consisted of 42 employees using total sampling technique. Data were collected through questionnaires and analyzed using simple linear regression. The results showed that HRM in waste management has a positive and significant effect on employee occupational health and safety with a t-value of 12.252 and a significance of 0.000. The R² value of 0.790 indicates a contribution of 79%.